The comparison of the efficacy and safety of intralesional triamcinolone acetonide and methotrexate injections for the treatment of fingernail psoriasis - Üstüner, Pelin; Balevi, Ali; Özdemir, Mustafa (Ankara University, 2018)
Objectives: Studies have demonstrated that the clinical efficacy and remission duration of intralesional corticosteroids in nail psoriasis are highly variable. Moreover, good clinical results have been reported after methotrexate injection in a case study with nail psoriasis. This study aimed to investigate the efficacy and safety of intralesional injection of triamcinolone acetonide and methotrexate in patients with fingernail psoriasis. Materials and Methods: Thirty-two patients diagnosed with fingernail psoriasis with at least three affected nails were included. Diluted triamcinolone acetonide, methotrexate and serum physiologic solution were randomly injected into three different fingernails having similar nail area psoriasis severity index (NAPSI) scores for four sessions. We compared the signs of nail matrix and nail bed involvement. The severity of fingernail psoriasis was investigated using NAPSI and modified NAPSI. Results: The responses evaluated by the NAPSI scores were similar in nails treated with methotrexate and triamcinolone acetonide. The improvement of the signs of nail matrix involvement was significantly higher in nails treated with methotrexate, but the improvement of the signs of nail bed involvement was similar in all groups. The improvement of onycholysis was significant only in nails treated with triamcinolone. On the other hand, the improvement of pitting and leukonychia were significant only in nails treated with methotrexate. Conclusion: Methotrexate injection might be a better treatment choice for fingernail psoriasis with the signs of nail matrix involvement and triamcinolone acetonide injection for the fingernail psoriasis with the signs of nail bed involvement.

Amaç: Çalışmalar tırnak psöriasisinde intralezyonel kortikosteroidlerin klinik etkinliği ve remisyon süresinin oldukça değişken olduğunu göstermektedir. Ayrıca, tırnak psöriasisli bir olgu raporunda metotreksat enjeksiyonundan sonra iyi klinik sonuçlar bildirilmiştir. Bu çalışma el tırnak psöriasisli hastalarda intralezyonel triamsinolon asetonit ve metotreksat enjeksiyonunun etkinlik ve güvenilirliğini araştırmayı amaçlamaktadır. Gereç ve Yöntem: En az üç tırnak tutulumu olan el tırnaklarında psöriasis tanısı olan otuz iki hasta çalışmaya dahil edildi. Benzer tırnak alan psoriasis şiddet indeks (NAPSI) skorları olan üç farklı el tırnağına sulandırılmış triamsinolon asetonit, metotreksat ve serum fizyolojik dört seans süresince rastgele enjekte edildi. Tırnak matriks ve tırnak yatak tutulum bulgularını karşılaştırdık. El tırnaklarının psoriasis şiddeti NAPSI ve modifiye NAPSI kullanılarak araştırıldı. Bulgular: Metotreksat ve triamsinolon asetonit ile tedavi alan tırnaklarda NAPSI skorları ile değerlendirilen yanıtlar benzer idi. Tırnak matriks tutulumu bulgularının iyileşmesi metotreksat ile tedavi edilen tırnaklarda anlamlı oranda daha fazla idi, ancak tırnak yatak tutulumu bulgularının iyileşmesi tüm gruplarda benzer idi. Onikolizin iyileşmesi yanlızca triamsinolon ile tedavi gören tırnaklarda anlamlı idi. Diğer yandan, pitting ve lökonişinin iyileşmeleri yanlızca metotreksat tedavisi alan tırnaklarda anlamlı idi. Sonuç: Metotreksat enjeksiyonu tırnak matriks tutulumu bulguları olan el tırnak psöriasisinde ve triamsinolon asetonit enjeksiyonu ise tırnak yatak tutulumu bulguları olan el tırnak psöriasisinde daha iyi bir tedavi seçeneği olabilir.
El tırnak psöriasisinin tedavisinde intralezyonel triamsinolon asetonit ve metotreksat enjeksiyonlarının etkinlik ve güvenilirliğinin karşılaştırılması
Keywords: Methotrexate; Psoriasis; Steroid; Metotreksat; Psöriasis; Steroid